Obtaining glucose-based 5-hydroxymethylfurfural on large-pore zeolites - Patrylak, Lyubov; Konovalov, Serhii; Pertko, Olexandra; Yakovenko, Anzhela; Povazhnyi, Volodymyr; Melnychuk, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2021)
Obtaining such substances-platforms as, in particular, 5-hydroxymethylfurfural is one of the areas most actively investigated at present. They can act as raw materials for the further production of a new generation of biopolymers, fuels, pharmaceuticals, dietary supplements, and other chemicals. This paper reports the catalysts, synthesized by using methods of ion exchange and impregnation, based on the large-pore zeolites X, Y, and M, which contain the cations of rubidium, lanthanum, calcium, and ammonium. It was found that the zeolites' specific surface was 400‒500 m2/g; the selected synthesis conditions did not cause noticeable destruction of the microporous structure. In the presence of the synthesized catalysts, glucose dehydration in the aqueous medium and in dimethyl sulfoxide was carried out at 150–160 °C. The higher efficiency of polycationic forms of zeolites in a non-aqueous medium has been established. In the latter case, a 40 % yield of 5-hydroxymethylfurfural was achieved at an almost complete glucose conversion. Deactivated catalyst samples were investigated using the methods of infrared spectroscopy and differential thermal analysis/thermogravimetry. It was found that the catalyst accumulates fewer oligomerization process by-products when the reaction is implemented in dimethyl sulfoxide. The loss of mass by the samples deactivated in an aqueous medium is 30‒33 %, while in dimethyl sulfoxide – up to 24 %. The obtained results are important for practical application as the only volatile conversion product is 5-hydroxymethylfurfural with a yield of up to 40 %. That is acceptable for the possible implementation of a one-stage process of obtaining 5-hydroxymethylfurfural in the future